(untitled) (Global Journal of Medical Research, 2014)
Skeletal Tuberculosis is a not that common nowadays due to effective antitubercular chemotherapy available along with the fact that most cases of primary tuberculosis are diagnosed quite ealy. Furthermore Presacral tubercular abscesses are a rare entity. Lumbosacral region is the least effected. We report a case of a patient with presacral abscess in a patient without any source of tuberculosis elsewhere. We present a rare case of large presacral abscess simulating a big tumor and MRI Done showed a large presacral abscess. It was managed by drainage through a trans pedicular route.